A mortalidade infantil e a relação com o espaço geografico na Cidade de Rio Claro, SP, BR - Vedovato, Maria Aparecida, 1953- (2009)
Orientadores: Roberto Wagner Lourenço, Maria Rita Donalisio Cordeiro